2022
DOI: 10.1163/22134808-bja10080
|View full text |Cite
|
Sign up to set email alerts
|

Odor-Induced Taste Enhancement Is Specific to Naturally Occurring Temporal Order and the Respiration Phase

Abstract: Interaction between odor and taste information creates flavor perception. There are many possible determinants of the interaction between odor and taste, one of which may be the somatic sensations associated with breathing. We assumed that a smell stimulus accompanied by inhaling or exhaling enhances taste intensity if the order is congruent with natural drinking. To present an olfactory stimulus from the identical location during inhalation and exhalation, we blocked the gap between the tube presenting the ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The surprising fact that many olfactory-gustatory interactions (Spence, 2012), such as the OITE effect (Spence, 2022b), appear relatively insensitive to the route of olfactory presentation (i.e., orthonasal or retronasal; though see Amano et al, 2022, for an isolated exception) may also fit in here. That said, one important difference from the example of voluntary mental imagery that was studied by Djordjevic and colleagues (2004a), and which can be elicited in the absence of any stimuli in the 'target' modality is that the OITE would appear to require a taste stimulus (Spence, 2022a).…”
Section: Chemosensory Interactions Involving Orthonasal Versus Retron...mentioning
confidence: 71%
See 1 more Smart Citation
“…The surprising fact that many olfactory-gustatory interactions (Spence, 2012), such as the OITE effect (Spence, 2022b), appear relatively insensitive to the route of olfactory presentation (i.e., orthonasal or retronasal; though see Amano et al, 2022, for an isolated exception) may also fit in here. That said, one important difference from the example of voluntary mental imagery that was studied by Djordjevic and colleagues (2004a), and which can be elicited in the absence of any stimuli in the 'target' modality is that the OITE would appear to require a taste stimulus (Spence, 2022a).…”
Section: Chemosensory Interactions Involving Orthonasal Versus Retron...mentioning
confidence: 71%
“…Somewhat surprisingly, OITE (as well as, as it happens, a number of other olfactory-gustatory interactions) appear to be unaffected by whether a given odorant happens to be experienced retronasally or orthonasally (Lawrence et al, 2009;Spence, 2012; though see Amano et al, 2022). This is surprising inasmuch as only retronasal olfaction is constitutively involved in multisensory flavour perception (see Spence et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the results of Amano et al. (2022) similarly showed that OITE depended on the time order of smell with breathing in natural drinking, and postnasal conditions were more prominent. Blankenship et al.…”
Section: Factors Affecting Odor‐induced Sweetness Enhancementmentioning
confidence: 92%
“…This led to the hypothesis that olfaction exists as a dual sensory modality 14 . Interestingly, it has recently been suggested that breathing (i.e., retronasal olfaction) is a strong determinant of odour‐taste interaction 15 and that ortho‐ and retronasal olfaction are complementary systems 16 …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] This led to the hypothesis that olfaction exists as a dual sensory modality. 14 Interestingly, it has recently been suggested that breathing (i.e., retronasal olfaction) is a strong determinant of odour-taste interaction 15 and that ortho-and retronasal olfaction are complementary systems. 16 However, among studies that specifically investigated perceptual differences (sensitivity, intensity and identification) in olfactory perception between the two pathways, results show some discrepancies.…”
mentioning
confidence: 99%